Applications of CRISPR/Cas9 in the Synthesis of Secondary Metabolites in Filamentous Fungi - Jiang, Chunmiao; Lv, Gongbo; Tu, Yayi; Cheng, Xiaojie; Duan, Yitian; Zeng, Bin; He, Bin (Frontiers in Microbiology, 2021)
Filamentous fungi possess the capacity to produce a wide array of secondary metabolites with diverse biological activities and structures, such as lovastatin and swainsonine. With the advent of the post-genomic era, increasing amounts of cryptic or uncharacterized secondary metabolite biosynthetic gene clusters are continually being discovered. However, owing to the longstanding lack of versatile, comparatively simple, and highly efficient genetic manipulation techniques, the broader exploration of industrially important secondary metabolites has been hampered thus far. With the emergence of CRISPR/Cas9-based genome editing technology, this dilemma may be alleviated, as this advanced technique has revolutionized genetic research and enabled the exploitation and discovery of new bioactive compounds from filamentous fungi. In this review, we introduce the CRISPR/Cas9 system in detail and summarize the latest applications of CRISPR/Cas9-mediated genome editing in filamentous fungi. We also briefly introduce the specific applications of the CRISPR/Cas9 system and CRISPRa in the improvement of secondary metabolite contents and discovery of novel biologically active compounds in filamentous fungi, with specific examples noted. Additionally, we highlight and discuss some of the challenges and deficiencies of using the CRISPR/Cas9-based genome editing technology in research on the biosynthesis of secondary metabolites as well as future application of CRISPR/Cas9 strategy in filamentous fungi are highlighted and discussed.